Analysis method based on laccase catalytic degradation of microplastics

By optimizing experimental conditions and combining high-efficiency detection technology, an analysis method based on laccase-catalyzed degradation of microplastics is provided, which solves the problems of low degradation efficiency and strong enzyme specificity in the existing technology, and achieves high-efficiency detection of a variety of plastics. Degradation and qualitative and quantitative analysis provide a sustainable new way to control plastic pollution.

CN119355172APending Publication Date: 2025-01-24NORTHWEST A & F UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411716645.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art lacks qualitative quantitative analysis methods for the efficiency of laccase degraded microplastics and their degradation products, resulting in low degradation efficiency and enzymes can only degrade single plastic components, limiting their wide application in the treatment of complex microplastic pollution.

Method used

An analysis method based on the catalytic degradation of microplastics by laccase is provided. By optimizing the experimental conditions for the degradation of microplastics by laccase and combining it with efficient detection technology, the chemical changes produced during the degradation process can be accurately and quantitatively analyzed. The method includes pretreatment of microplastic particles, determination of optimal experimental conditions for laccase degradation of microplastics, degradation experiments in a constant-temperature oscillator, regular sampling and analysis, and ultra-high performance liquid chromatography-quadrupole-time-of-flight mass spectrometry. Samples were analyzed using technology (UPLC-Q-TOF-MS).

Benefits of technology

Achieved the qualitative and quantitative analysis of the micro -plastic degradation of paint enzymes, improved the degradation efficiency, can effectively degrade a variety of plastic, provides key data support for micro -plastic biodegradation mechanisms, and provides a new new development of plastic pollution treatment. way.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119355172A_ABST
    Figure CN119355172A_ABST
Patent Text Reader

Abstract

The invention discloses an analysis method for catalytically degrading microplastics based on laccase. The analysis method comprises the following steps: pretreating microplastic particles; determining an optimal experiment condition for degrading the microplastics by the laccase; uniformly mixing the pretreated micro-plastic with the determined laccase solution under the optimal experiment condition according to a certain proportion, carrying out a degradation experiment in a constant-temperature oscillator, and regularly sampling and analyzing; the reaction suspension obtained after regular sampling is filtered through a filter membrane, supernate and solid are obtained, the supernate is used for degradation product analysis, and the solid is used for physicochemical characteristic characterization analysis; and analyzing the sample by using an ultra-high performance liquid chromatography-quadrupole-time-of-flight mass spectrometry technology. According to the qualitative and quantitative analysis method based on laccase catalytic degradation of the microplastics, the experiment conditions of laccase degradation of the microplastics are optimized, an efficient detection technology is combined, and compound variants generated in the degradation process can be accurately and quantitatively analyzed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of biodegradation of plastic pollution, and in particular to an analytical method based on laccase-catalyzed degradation of microplastics. Background Art

[0002] Plastic pollution has become a major threat to the environment and ecosystem worldwide. Since plastics are usually chemically inert and highly resistant to biodegradation, a large amount of plastic waste has accumulated in the environment for a long time, posing a huge challenge to the natural ecological balance. At present, the annual global plastic production has exceeded 380 million tons, and by 2015, the total global plastic production had reached 8.3 billion tons. As a common thermoplastic, PE is widely used in disposable plastic bags, cling film, agricultural mulch film and other fields; PET is mainly used in the production of foam plastics, disposable tableware, building insulation materials and various packaging products; PLA is also widely used in food packaging, agricultural films, 3D printing and other fields due to its biodegradability. However, with the production and use of a large number of PE, PET and PLA products, the long-term accumulation of these plastics in the natural environment poses a serious threat to the global ecosystem.

[0003] Traditional methods for plastic pollution control mainly include landfill, incineration, thermal cracking and secondary processing, but these methods have many disadvantages, such as high processing cost, high energy consumption, easy to produce secondary pollution, etc., which are not conducive to sustainable development. In this context, biodegradation, as a green and environmentally friendly solution, shows great application potential due to its advantages such as low energy consumption and non-toxic byproducts. However, the existing bioenzymatic degradation technology for PE, PET and PLA plastics still faces multiple challenges, such as low degradation efficiency and strong enzyme specificity. Usually, it can only degrade a single plastic component, which limits its wide application in the control of complex microplastic pollution. Therefore, it is of great significance to develop a biodegradation method that can efficiently degrade multiple plastics (such as PE, PET and PLA). This can not only improve the biodegradation efficiency of plastic waste, but also provide a new way to achieve sustainable development in dealing with global plastic pollution. Summary of the invention

[0004] The embodiments of the present application provide an analysis method based on laccase-catalyzed degradation of microplastics, which solves the technical problem that there is a lack of qualitative and quantitative analysis methods for the efficiency of laccase-catalyzed degradation of microplastics and their degradation products in the prior art, resulting in low degradation efficiency and the enzyme can only degrade a single plastic component, limiting its wide application in the management of complex microplastic pollution. A qualitative and quantitative analysis method based on laccase-catalyzed degradation of microplastics is provided. By optimizing the experimental conditions for laccase-catalyzed degradation of microplastics and combining it with efficient detection technology, it is possible to accurately and quantitatively analyze the changes in compounds produced during the degradation process, providing key data support for further research on the biodegradation mechanism of microplastics.

[0005] An embodiment of the present invention provides an analysis method based on laccase-catalyzed degradation of microplastics, including pretreatment of microplastic particles; determining the optimal experimental conditions for laccase degradation of microplastics; mixing the pretreated microplastics with the laccase solution under the determined optimal experimental conditions in a certain proportion, conducting a degradation experiment in a constant temperature oscillator, and taking samples for analysis at regular intervals; filtering the reaction suspension collected by regular sampling through a filter membrane to obtain a supernatant and a solid, the supernatant being used for degradation product analysis, and the solid being used for physicochemical property characterization analysis; analyzing the sample by ultra-high performance liquid chromatography-quadrupole-time of flight mass spectrometry (UPLC-Q-TOF-MS), and eliminating the interference of background compounds by excluding molecular formulas with a sample to blank peak intensity ratio of less than 20.

[0006] In one possible implementation, the pretreatment of the microplastic particles includes obtaining a variety of microplastic powders with particle sizes required for the experiment after sieving; washing the sieved microplastic powders three times each with anhydrous ethanol and deionized water, and then drying them for degradation experiments.

[0007] In one possible implementation, determining the optimal experimental conditions for laccase degradation of microplastics includes optimizing three key parameters: pH, temperature, and laccase concentration, and the optimal values ​​of the three key parameters are pH 7, temperature 40°C, and laccase concentration 1.5U / mL.

[0008] In a possible implementation, the reaction suspension needs to be subjected to preliminary solid-liquid separation by centrifugation before being filtered through a membrane; the membrane filtration includes first filtering the degraded reaction suspension using a PTFE membrane of the size required for the experiment to remove plastic particles, and then using a Vivaspin 20,3kDa MWCO polyethersulfone membrane to remove the enzyme in the solution to obtain the supernatant, which is used for the analysis of the degradation products; the solid is washed three times with an SDS solution and then subjected to characterization analysis.

[0009] In a possible implementation, the sample analysis by ultra-high performance liquid chromatography-quadrupole-time of flight mass spectrometry (UPLC-Q-TOF-MS) also includes enriching the plastic extract using a Waters Oasis HLB Plus solid phase extraction column, eluting with 5 mL of ethyl acetate / methanol in a 1:1 mixed solution, and finally concentrating the extract to 1 mL under a nitrogen flow for UPLC-Q-TOF-MS analysis.

[0010] In one possible implementation, the HPLC-QTOF-MS data are peak detected and calibrated using Compound Discoverer 2.0 software to obtain a peak area list with the following settings: a signal-to-noise ratio (S / N) threshold of 6, a mass tolerance of 5 ppm, a maximum retention time shift of 0.5 minutes, and a minimum peak intensity of 1×10 6 The molecular formulas with scores greater than 70 were regarded as preliminarily identified chemical substances, and the compounds with accurate mass matches were searched in the ChemSpider database, and the ion fragments were compared in combination with existing research or open mass spectrometry databases to obtain the final products.

[0011] One or more technical solutions provided in the embodiments of the present invention have at least the following technical effects or advantages:

[0012] The embodiments of the present invention provide a qualitative and quantitative analysis method based on laccase-catalyzed degradation of microplastics. By optimizing the experimental conditions for laccase degradation of microplastics and combining it with efficient detection technology, it is possible to accurately and quantitatively analyze the changes in compounds produced during the degradation process, providing key data support for further research on the biodegradation mechanism of microplastics.

[0013] The embodiment of the present invention is simple and reasonable to operate and is a simple and rapid analysis method.

[0014] The embodiments of the present invention propose a new PET degradation mechanism other than hydrolysis, namely, accelerating the degradation of microplastics through oxidation.

[0015] The embodiments of the present invention provide a potential new approach for plastic pollution control and provide a reasonable and effective means to solve the environmental and biological safety issues of microplastics that are closely related to our lives. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments of the present invention or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 is the relative laccase activity measured under different conditions (pH, temperature, laccase concentration);

[0018] Figure 2 The mass loss changes of microplastics after degradation in the presence or absence of laccase in the embodiments of the present invention;

[0019] Figure 3The particle size changes of microplastics in the embodiments of the present invention before and after degradation under the conditions of laccase or without laccase;

[0020] Figure 4 The SEM images of microplastics in the embodiments of the present invention before and after degradation in the presence or absence of laccase;

[0021] Figure 5 FTIR spectra of microplastics before and after degradation in the presence or absence of laccase in an embodiment of the present invention;

[0022] Figure 6 The carbonyl index changes of microplastics in the embodiments of the present invention before and after degradation under the conditions of laccase or without laccase;

[0023] Figure 7 The molecular weight changes of the microplastics in the embodiments of the present invention before and after degradation under the conditions of laccase or without laccase, including the number average molecular weight (Mn), weight average molecular weight (Mw) and peak average molecular weight (Mp);

[0024] Figure 8 This is the m / z distribution characteristic of the product molecular signal after the microplastics in the embodiment of the present invention are degraded in the presence or absence of laccase. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In the description of the embodiments of the present invention, it should be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present invention and simplifying the description, rather than indicating or implying that the devices or elements referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limitations on the present invention. The terms "first", "second", and "third" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance. In addition, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be a connection between the two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present invention can be understood according to the specific circumstances.

[0027] The present application embodiment provides a method for analyzing the degradation of different types of microplastics by laccase, comprising the following steps:

[0028] S1. Pretreatment of microplastic particles:

[0029] After sieving with a sieve, PE, PET and PLA powders with a particle size of 75 μm were obtained. In the embodiment of the present application, sieves of different particle sizes can be selected for sieving according to different experimental requirements. The various microplastics in the embodiment of the present application include PE, PET and PLA powders. In the embodiment of the present application, PE, PET and PLA powders are used as examples for degradation analysis;

[0030] The sieved PE, PET and PLA powders were washed three times with anhydrous ethanol and deionized water respectively and dried for degradation experiments;

[0031] S2. The process of screening the best experimental conditions for laccase degradation of microplastic particles mainly includes the optimization of three key parameters: pH, temperature and laccase dosage:

[0032] By setting different pH values ​​(4.0, 5.0, 6.0, 7.0, 8.0, 9.0), the activity of laccase in different acid-base environments was determined to find out its most suitable pH range;

[0033] The activity of laccase was evaluated under different temperature conditions (20℃, 30℃, 40℃) to determine its optimal catalytic degradation temperature;

[0034] Different laccase concentrations (such as 1.0U / mL, 1.5U / mL, and 2.0U / mL) were set to analyze the changing trends of laccase activity and degradation efficiency with laccase concentration, and to determine the most effective laccase dosage while ensuring efficient degradation;

[0035] Laccase activity assay:

[0036] The activity of laccase was determined by measuring the concentration of ABTS free radicals at room temperature, using a UV-visible spectrophotometer to measure the absorbance at 420 nm, and the enzyme activity was calculated by the absorbance change caused by ABTS oxidation;

[0037] S3. Microplastic degradation:

[0038] PE, PET, and PLA particles (1 g / L) were mixed with laccase in a certain ratio and then placed in a constant temperature oscillator in the dark to simulate biological conditions, and the filtrate and degraded particles (solids) were collected regularly;

[0039] Analyze the changes in surface morphology, particle size and molecular weight of microplastics before and after degradation;

[0040] When determining the degradation efficiency, the PE, PET, and PLA pellets were weighed before and after the degradation experiment to obtain the mass loss.

[0041] Analyze the changes in the functional groups, elemental content, carbonyl index and other characteristics of degraded microplastics;

[0042] S4. The microplastic reaction solution was detected using ultra-high performance liquid chromatography-quadrupole-time of flight mass spectrometry (UPLC-Q-TOF-MS) to identify the molecular mass distribution and changes of the compound degradation products.

[0043] In the specific embodiment of the present application, the process of laccase degradation of microplastics is as follows:

[0044] The purchased PE, PET and PLA powders were first sieved to obtain microplastic particles with a particle size of 75 μm, and then washed with anhydrous ethanol and deionized water for multiple times to remove surface impurities. They were then dried at 45°C to constant weight for later use.

[0045] Prepare PBS (50mM) buffer solution. Dissolve 0.89g Na2HPO4·2H2O in 100mL deionized water to obtain solution 1. Dissolve 0.69g NaH2PO4·H2O in 100mL deionized water to obtain solution 2. Mix solution 1 and solution 2, and adjust the pH to the target pH with HCl solution (1M) or NaOH solution (1M) to obtain the final PBS buffer solution. Prepare the buffer solution before use.

[0046] Prepare ABTS (1mM) solution and acetic acid-sodium acetate buffer solution (0.1M, pH=4.2). At room temperature, take a certain amount of laccase solution, add it to 3mL of acetic acid-sodium acetate buffer solution, then add 1.0mL of ABTS solution, and measure the change of absorbance at 420nm within 5 minutes by UV-visible spectrophotometer. The amount of laccase required to oxidize 1μM ABTS per minute is 1 enzyme activity unit (U).

[0047] Laccase was added to PBS buffer solution to obtain laccase solutions of different concentrations (1.0U / mL, 1.5U / mL and 2.0U / mL). The enzyme activity of laccase at different concentrations was evaluated at 25°C, and the experiment was repeated three times. The optimal concentration was 1.5U / mL by calculating the relative activity of laccase. Figure 1 As shown in a.

[0048] The PBS buffer solution was adjusted to different pH values ​​by adding HCl solution or NaOH solution, and the concentration of laccase solution was 1.5U / mL. The laccase activity under different pH conditions was evaluated at 25°C, and the experiment was repeated three times. The optimal pH was 7.0 by calculating the relative activity of laccase. Figure 1 As shown in b.

[0049] The laccase solution with pH 7.0 and concentration of 1.5U / mL was selected to evaluate the laccase activity at different temperatures at 20℃, 30℃ and 40℃. The experiment was repeated three times. By calculating the relative activity of laccase, it was found that the optimal reaction temperature was 40℃. Figure 1 As shown in c.

[0050] The microplastic degradation experiment was carried out in a 30 mL amber glass bottle containing 20 mL of reaction mixture. PE, PET and PLA powders (1 g / L) were mixed with laccase solution and placed in a constant temperature oscillator and incubated at 150 rpm for 10 days in the dark. Unless otherwise specified, all reactions were performed under the optimal reaction conditions: pH 7.0, laccase solution concentration of 1.5 U / mL, and reaction temperature of 40 °C.

[0051] To verify the catalytic degradation performance of laccase on microplastics in the examples of this application, the samples of laccase-degraded microplastics in the examples were analyzed and measured. Figure 2-Figure 8 shown.

[0052] from Figure 2 It can be seen that under the condition of pH 7, the presence of laccase significantly promoted the mass loss of microplastics. Within 10 days, the mass of PLA decreased by about 12%, PET decreased by about 7%, and the mass change of PE was the smallest. Compared with the microplastic system without enzyme, PLA and PET also showed significant mass loss at pH 9. However, due to the more stable chemical structure of PE, its degradation effect is relatively limited.

[0053] from Figure 3 It can be seen that, whether it is PE, PLA or PET system, the particle size in the control group and the enzyme treatment group is reduced compared with the original microplastics. The formation of nanoplastics is closely related to the pH value, and shows a consistent trend in the degradation process of the three microplastics. Especially under the condition of pH 7, the addition of laccase significantly accelerated the reduction of microplastic particle size, followed by the condition of pH 5. In the degradation experiment at pH 7, by the 10th day, nanoparticles with a diameter of 339.1nm were detected in the PLA group, the size of PET particles was reduced to 464.2nm, and the size of PE particles was reduced to 1025.0nm.

[0054] from Figure 4It can be seen that the original microplastic surface is relatively smooth. As the degradation time increases, the surface of the three microplastics gradually becomes rough, and the degree of surface wear is significantly increased. Compared with the control group, the surface of the microplastics treated with laccase has undergone more significant changes, which are manifested in the formation of cracks, pores and the appearance of small particles. This result is consistent with the trend of particle size reduction mentioned above, indicating that PE, PET and PLA have all experienced varying degrees of degradation. It is worth noting that the surface change of PLA is the most significant, followed by PET, while the surface change of PE is the smallest.

[0055] from Figure 5 It can be seen that after the reaction of PE with laccase, the characteristic peaks of OH and CO and the bending and vibration of the methyl (-CH3 / -CH2-) group appear. The enhancement of the absorption peak may be due to the change of the polymer chain structure caused by oxidation. During the degradation process of PET, 3355, 1720, 1575 and 1020 cm - The peaks at 1240 cm-1 and 1370 cm-2, which are associated with the stretching vibration of the ester group (CO), are enhanced, corresponding to the OH, C=O, CH, and CO groups, respectively. - The peak intensity at 723 cm - The peak intensity corresponding to the CH bending vibration of the benzene ring in PET decreased, indicating that the benzene ring structure was degraded or changed due to the laccase-induced decomposition. After laccase-promoted biodegradation of PLA, the peaks at 3417, 2977, 2935, 1452, 1380, 1724, 1280, 1054, and 979 cm - The peak at 1 changed significantly, and these peaks corresponded to OH, CH, C=O and CO bonds. In contrast, all oxygen-containing peaks in the laccase-treated group were stronger than those in the treated group, indicating that the presence of laccase caused oxidation of microplastics.

[0056] from Figure 6 The changing trend of the carbonyl index (CI) index can be seen. Compared with PE microplastics, the CI values ​​of PET and PLA increased significantly during laccase treatment, indicating that the oxidative effect of laccase gradually increased during the 10-day degradation process.

[0057] from Figure 7It can be seen that GPC analysis shows that for PE, PET and PLA microplastics with a higher molecular weight distribution, only some molecular weight reduction was observed in the microplastic group, which may be caused by hydrolysis, that is, water molecules attack the polymer chain, resulting in chain breakage and molecular weight reduction. When microplastics coexist with laccase, the reduction in molecular weight is more obvious. After biodegradation, the Mn, Mw and Mp of PLA and PET decreased from 269,355 and 15,310 g / mol, 652,872 and 39,440 g / mol, 584,254 and 35,469 g / mol to 228,469 and 13,300 g / mol, 557,790 and 36,198 g / mol, 529,440 and 34,189 g / mol, respectively. Compared with the control group, the decrease rates of Mn, Mw and Mp of PLA and PET after laccase treatment increased by 11.54%, 8.01% and 5.57%, and 9.25%, 7.18% and 2.41%, respectively. These results show that laccase, as a biocatalyst, can not only promote the breakage of polymer chains, but also accelerate the degradation of microplastics through oxidation, further reducing the molecular weight, especially in the degradation of PLA and PET, the molecular weight distribution decreased significantly, accelerating its degradation process.

[0058] from Figure 8 It can be seen that after laccase treatment, PE microplastics showed a small change in the lower mass number range (100-300m / z), while a clear strong peak appeared in the higher mass number range (400-600m / z). This may mean that laccase triggered the degradation of certain macromolecules during the degradation of PE, generating degradation products of a specific mass. The samples of PET microplastics treated with laccase showed a significant increase in peaks, with a significant peak appearing in the low mass number region (100-400m / z), especially at about 350m / z. This indicates that PET underwent a more obvious degradation reaction under the action of laccase, generating relatively small degradation products. PLA samples showed more peaks in the low mass number region (100-400m / z), showing that laccase significantly accelerated the degradation of the polymer during the degradation of PLA and generated smaller molecular products. In short, the degradation effect of laccase on PET and PLA is more obvious, leading to the generation of small molecular weight compounds.

[0059] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other. Each embodiment focuses on the differences from other embodiments.

[0060] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. An analytical method based on laccase-catalyzed degradation of microplastics, characterized in that: include Pretreatment of microplastic particles; Determine the optimal experimental conditions for laccase degradation of microplastics; The pretreated microplastics are uniformly mixed with the laccase solution under the determined optimal experimental conditions, a degradation experiment is performed in a constant temperature oscillator, and samples are taken and analyzed regularly; The reaction suspension collected by periodic sampling is filtered through a filter membrane to obtain a supernatant and a solid, wherein the supernatant is used for degradation product analysis, and the solid is used for physical and chemical property characterization analysis; The microplastic degradation product samples were analyzed by ultra-performance liquid chromatography-quadrupole-time of flight mass spectrometry (UPLC-Q-TOF-MS), and the interference of background compounds was eliminated by excluding molecular formulas with a sample to blank peak intensity ratio of less than 20.

2. The analytical method based on laccase-catalyzed degradation of microplastics according to claim 1, characterized in that: The pretreatment of the microplastic particles includes After sieving with a sieve, various microplastic powders with the particle sizes required for the experiment were obtained; The screened microplastic powders were washed three times with anhydrous ethanol and deionized water respectively, and then dried for degradation experiments.

3. The analytical method based on laccase-catalyzed degradation of microplastics according to claim 1, characterized in that: The optimal experimental conditions for determining the degradation of microplastics by laccase include The three key parameters of pH, temperature and laccase concentration were optimized, and the optimal values ​​of the three key parameters were obtained to be pH 7, temperature 40° C. and laccase concentration 1.5 U / mL.

4. The analytical method based on laccase-catalyzed degradation of microplastics according to claim 1, characterized in that: The reaction suspension needs to be centrifuged for preliminary solid-liquid separation before being filtered through the filter membrane; The membrane filtration comprises first filtering the reaction suspension after degradation using a PTFE filter membrane of a size required for the experiment to remove plastic particles, and then using a Vivaspin 20,3kDa MWCO polyethersulfone membrane to remove the enzyme in the solution to obtain the supernatant, which is used for the degradation product analysis; The solid was washed three times with SDS solution and then characterized and analyzed.

5. The analytical method based on laccase-catalyzed degradation of microplastics according to claim 1, characterized in that: The method further comprises the following steps before analyzing the sample by ultra-high performance liquid chromatography-quadrupole-time of flight mass spectrometry (UPLC-Q-TOF-MS): Microplastic degradation products were enriched using a Waters Oasis HLB Plus solid phase extraction column and eluted with 5 mL of a 1:1 mixed solution of ethyl acetate / methanol. Finally, the extract was concentrated to 1 mL under a nitrogen flow for UPLC-Q-TOF-MS analysis.

6. The analytical method based on laccase-catalyzed degradation of microplastics according to claim 1, characterized in that: It also includes peak detection and calibration of HPLC-Q-TOF-MS data using Compound Discoverer 2.0 software to obtain peak area lists with the following settings: signal-to-noise ratio (S / N) threshold of 6, mass tolerance of 5 ppm, maximum retention time shift of 0.5 min, and minimum peak intensity of 1 × 10 6 ; Molecular formulas with scores greater than 70 were regarded as preliminarily identified chemical substances, and compounds with accurate mass matches were searched in the ChemSpider database, and ion fragment comparisons were performed in combination with existing research or open mass spectrometry databases to obtain the final product.